2017
DOI: 10.3184/175815617x14799886573101
|View full text |Cite
|
Sign up to set email alerts
|

Change of Feeding Strategy Prior to Migration: A Comparative Diet Analysis in the Lesser Kestrel (Falco Naumanni)

Abstract: Assessing the variation in diet composition of a species, over different years and between periods, offers insights to comprehend its ecological niche as well as to define different feeding strategies. We studied the diet of the Lesser Kestrel ( Falco naumanni) by analysing 1040 regurgitated pellets collected in the city of Ioannina (northwestern Greece). We compared diet composition between the breeding period (data from years 2010–2015) and the pre-migration period (data from 2013–2015) at the study site. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Movements of breeding adults are limited mainly to within 3 km from their colony during nest attendance (Bondì & Sarà, ; Cecere et al, ; Gustin, Giglio, Pellegrino, Frassanito, & Ferrarini, ; Tella, Forero, Hiraldo, & Donázar, ; Vlachos et al, ). Chicks are therefore mainly fed with prey collected in the immediate area surrounding the colony (Bounas & Sotiropoulus, ; Morganti, Franzoi, Bontempo, & Sarà, ). After breeding, they move to premigratory areas in Sicily, where they stay from late June to mid‐October fattening before migration (Bounas & Sotiropoulus, ; Sarà et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Movements of breeding adults are limited mainly to within 3 km from their colony during nest attendance (Bondì & Sarà, ; Cecere et al, ; Gustin, Giglio, Pellegrino, Frassanito, & Ferrarini, ; Tella, Forero, Hiraldo, & Donázar, ; Vlachos et al, ). Chicks are therefore mainly fed with prey collected in the immediate area surrounding the colony (Bounas & Sotiropoulus, ; Morganti, Franzoi, Bontempo, & Sarà, ). After breeding, they move to premigratory areas in Sicily, where they stay from late June to mid‐October fattening before migration (Bounas & Sotiropoulus, ; Sarà et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Chicks are therefore mainly fed with prey collected in the immediate area surrounding the colony (Bounas & Sotiropoulus, ; Morganti, Franzoi, Bontempo, & Sarà, ). After breeding, they move to premigratory areas in Sicily, where they stay from late June to mid‐October fattening before migration (Bounas & Sotiropoulus, ; Sarà et al, ). Migration of this species is quite fast, and the journey from pre‐migratory areas to winter quarters takes only a few days.…”
Section: Methodsmentioning
confidence: 99%
“…There they exploit the temporal abundance of food resources, mainly insects, so as to build up the appropriate fat reserves and replace – at least partially - their flight feathers (i.e. moult) 37 39 . It has also been suggested that such gatherings may facilitate the selection of future breeding habitats and aid spring navigation 40 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, O. tarda , T. tetrax and F. naumanni consume orthopterans during the breeding and pre-migration periods ( Rocha et al 2005 , Jiguet 2002 , Catry et al 2014 , Bounas and Sotiropoulosa 2017 ). Despite its importance, to date no comprehensive inventory on Orthoptera fauna has been performed in Castro Verde SPA .…”
Section: Introductionmentioning
confidence: 99%